Cloud Computing: Revolutionizing Enterprise Data with Integration and Real-time Insights - Sai Kiran Karumuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of cloud computing on enterprise data management, focusing on how organizations are leveraging cloud-native technologies to overcome traditional data silos and enhance operational efficiency. The article explores key benefits including improved scalability, enhanced data integration capabilities, and real-time analytics, supported by case studies from manufacturing and financial sectors. Through comprehensive analysis of security frameworks, change management strategies, and implementation best practices, the article demonstrates how cloud computing is enabling organizations to achieve better decision-making capabilities, operational agility, and competitive advantages. The article also investigates emerging trends and future implications of cloud technologies, highlighting the critical role of proper implementation strategies and security measures in successful cloud adoption.